Analisis Peran Dinas Tenaga Kerja dalam Upaya Mengurangi Masalah Pengangguran Terdidik di Kota Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The unemployment problem in Indonesia is still high and is a challenge that must be overcome. Unemployment with a high number in Kupang City is educated unemployment where individuals who have a high level of education but have not found work that matches their skills. This study is a qualitative descriptive study. Data collection used in-depth interviews, observation and documentation. Then analyzed using qualitative analysis. The results of this study indicate that the Role of the Manpower Office in overcoming educated unemployment in Kupang City consists of 3 sides, namely the first side is Education, the Manpower and Transmigration Office has taken various strategic steps such as re-arranging competency-based curriculum, market demand-based training, internships, and developing a digital job matching system. The second is Skills Training, Skills training in Kupang City is an important investment in increasing the competitiveness of the workforce, especially college graduates who do not yet have practical skills. The work equipment provision program by the Kupang City Manpower Office is a strategic step to encourage independence and reduce unemployment, especially educated unemployment. The third is Work Experience, this program has had a real impact, such as increasing participant work readiness and recruitment opportunities by companies. However, the implementation of the program still faces obstacles, especially in terms of the non-digital administration system, ineffective communication with corporate partners, and uneven mentor guidance.